Análise numérica de conectores parafusos em pilares mistos circulares preenchidos com concreto - Lucas Ribeiro dos Santos (2017)
This study has the main goal evaluate the behavior of high strength bolts connectors applied in concrete-filled steel columns (CFSC). The usage of bolts as shear connectors can be regarded as a viable solution and with a great practical interest, once the bolts are easily installed in the CFSCs and are considered low-cost technology. In this study, shear tests were performed using bolts connectors on concrete-filled steel columns. The experimental tests were analyzed, mainly, considering the outputs obtained from load versus slip curves. Then, a numerical study was carried out using the finite element software ABAQUS. The numerical model was calibrated considering experimental data and it was able to reproduce the specimen behavior observed during tests. For the constitutive laws of the material concrete, three types, of uniaxial compression stress versus deformation curves were analyzed. These analyses showed in a good approximation for the behavior of the concrete under confinement. The validation of the numerical results was consolidated by a critical and comparative analysis of the load versus slip curves obtained experiment and numerically. Then, parametric study of the bolts as connectors was carried out considering the following parameters: length and diameter of bolts, diameter of CFSCs, material properties and height levels were bolts were set up. Finally, an analytical model was developed for the estimation of the strength of bolts shear connectors. The proposed model was based on prescriptions of the European standard for steel and composite steel and concrete structures, providing adequate results, with lower variation coefficients if compared to other analytical models found in the literatures, the proposed model by Brazilian standard